Leber congenital amaurosis: A clinical and genetic study from a tertiary eye care center - Abhishek Upadhyaya; Srikanta Kumar Padhy; Nithin Teja; Goura Chattannavar; Shreya Dutta; Venkatesh Pochaboina; Jeyapoorani Balasubramanian; Chitra Kannabiran; Brijesh Takkar; Manjushree Bhate; Subhadra Jalali; Deepika C Parameswarappa (Indian Journal of Ophthalmology)
Purpose: To assess the clinical phenotypes and genetic mutations in patients with Leber congenital amaurosis (LCA) from a tertiary eye care center in India. Design: Retrospective observational study. Methods: The study includes patients with a clinical diagnosis of LCA who underwent genetic testing from January 2016 to December 2021. The clinical exome of the patients was analyzed by targeted next-generation sequencing. The genetic variants found were classified as per standard American College of Medical Genetics and Genomics (ACMG) criteria and ClinVar database. Results: There were 35 patients (19 females, 16 males) of LCA. Family history was positive in 29% (10/35) and a history of consanguinity was noted in 54% (19/35) of the patients. The mean presenting best-corrected visual acuity was 2.48 ± 0.59 logMAR. Retinal pigment epithelial abnormalities and macular involvement were seen in 83% (58/70) and 23% (16/70) of the eyes, respectively, at presentation. The most common causative genes for LCA in our cohort were: GUCY2D (20%, 7/35), CRB1 (14%, 5/35), RPE65 (11%, 4/35), RPGRIP1 (11%, 4/35), and LCA5 (9%, 3/35). Autosomal recessive inheritance was seen in 94% (33/35). Macular involvement at presentation was seen in CRB1 (3/5), NMNAT1 (2/2), and one each of RPE65, LCA5, and RDH12 patients. The genetic testing cost was reduced from 23,800 INR to 15,000 INR per test in the study duration. Conclusions: Genetic screening of LCA cases identified various genotypes, with GUCY2D being the most common. Increased awareness and reduced costs of genetic testing would benefit both patients and caregivers. With promising clinical trial outcomes, genotyping is crucial for better patient selection and treatment.